2017
DOI: 10.1155/2017/5023680
|View full text |Cite
|
Sign up to set email alerts
|

T Helper Lymphocyte and Mast Cell Immunohistochemical Pattern in Nonceliac Gluten Sensitivity

Abstract: Background and Aims Nonceliac gluten sensitivity (NCGS) is a gluten-related emerging condition. Since few data about NCGS histopathology is available, we assessed the markers of lymphocyte and innate immunity activation. Materials and Methods We retrieved duodenal biopsy samples of patients with NCGS diagnosis according to the Salerno criteria. We selected specimens of positive (seropositive celiac disease/Marsh 1-2 stage) and negative (normal microscopic picture) controls. Immunohistochemistry for CD3 (intrae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 34 publications
2
16
0
1
Order By: Relevance
“…Therefore, histopathology could represent a very appealing field of study. In this regard, we recently demonstrated, by immunohistochemistry, a rise in CD117+ cells in the lamina propria of patients with NCGS [4]. CD117 may identify mast cells; consequently, this result seems to be in agreement with that of Zanini et al, who found, in most cases, an increase in eosinophil count (more than five eosinophils in the lamina propria per high power field) when compared to the control group, where this finding was absent.…”
Section: Dear Editorsupporting
confidence: 91%
“…Therefore, histopathology could represent a very appealing field of study. In this regard, we recently demonstrated, by immunohistochemistry, a rise in CD117+ cells in the lamina propria of patients with NCGS [4]. CD117 may identify mast cells; consequently, this result seems to be in agreement with that of Zanini et al, who found, in most cases, an increase in eosinophil count (more than five eosinophils in the lamina propria per high power field) when compared to the control group, where this finding was absent.…”
Section: Dear Editorsupporting
confidence: 91%
“…We thank the authors for agreeing on many of the histopathological and clinical points that result from our experience, partially confirmed in their publication [2], and for their letter of comment when they write Bsupport an additional hypothesis about NCGS pathogenesis: an allergic intolerance to foods other than wheat.T he interesting point of this publication is that it highlights the number of mast cells (CD117+) as a marker of NCGS. In our opinion, the elevated number of mast cells is due to the increased number of eosinophils, which is a common feature of NCGS patients describe in our study [1].…”
Section: Dear Editorsupporting
confidence: 56%
“…However, no study has so far analyzed in depth the nature of this association. The available data relies mainly on observational studies aiming to elucidate the prevalence of this condition, which ranges around the 25%[ 3 - 8 , 34 , 35 ]. However, the lack of case-control studies is a serious limitation to ascertain the reliability of the association.…”
Section: Neurologic and Psychiatric Manifestationsmentioning
confidence: 99%